2009
DOI: 10.1039/b906021a
|View full text |Cite
|
Sign up to set email alerts
|

Chiral recognition of 2-(3-benzoylphenyl)propionic acid (ketoprofen) by serum albumin: an investigation with microcalorimetry, circular dichroism and molecular modelling

Abstract: The interaction of enantiomeric ketoprofen (KP) with BSA and HSA was studied by isothermal titration calorimetry (ITC). Affinity constants and thermodynamic parameters for complexation in two main protein sites were determined. Affinity constants for both proteins are generally lower for S(+)- than for R(-)-KP. Large enthalpic contributions to Gibbs free energy are compensated by large negative entropic terms for S(+) in the BSA-subdomain IIIA and HSA-subdomain IIA. The lowest energy BSA complexes of both enan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 31 publications
1
38
0
Order By: Relevance
“…In the last decade, several models have been developed to study the binding between HSA and restricted drug families 45,46,47 , and a few global models have been developed based on different approaches, such as genetic function approximation, multiple linear regression, heuristic regression procedures and ant colony systems 48,49,50 . Monti et al combined molecular mechanisms (MM) and molecular dynamics (MD) with circular dichroism (CD) to identify the main interactions between ketoprofen enantiomers and the surrounding amino acids at short distances in bovine serum albumin 51 . Similarly, Yu et al took advantage of MM and MD to identify several key residues that are involved in the enantioselectivity for the binding of AGP to mexiletine enantiomers, such as Arg90 43 .…”
Section: Methods and Modelsmentioning
confidence: 99%
“…In the last decade, several models have been developed to study the binding between HSA and restricted drug families 45,46,47 , and a few global models have been developed based on different approaches, such as genetic function approximation, multiple linear regression, heuristic regression procedures and ant colony systems 48,49,50 . Monti et al combined molecular mechanisms (MM) and molecular dynamics (MD) with circular dichroism (CD) to identify the main interactions between ketoprofen enantiomers and the surrounding amino acids at short distances in bovine serum albumin 51 . Similarly, Yu et al took advantage of MM and MD to identify several key residues that are involved in the enantioselectivity for the binding of AGP to mexiletine enantiomers, such as Arg90 43 .…”
Section: Methods and Modelsmentioning
confidence: 99%
“…The results showed that K SV values varied according to temperature, with K SV values decreasing as the temperature increased. As we know, dynamic quenching depends on diffusion, and the coefficient of diffusion will augment with the increase of temperature [41]. However, for static quenching, the stability of complex formations will decrease with the increase of temperature, so the quenching constant is inversely correlated with temperature [27].…”
Section: Mechanism Of Fluorescence Quenchingmentioning
confidence: 98%
“…Many small molecules like drugs, dyes etc. bind to cellular serum proteins to exert their adverse and normal functions and a large number of studies have been recently undertaken in this direction [1][2][3][4][5][6][7][8][9][10][11][12]. Small dye molecules can be potentially dangerous to our environment and many living objects due to toxic, carcinogenic and polluting properties, nevertheless they are being widely used in our day today life.…”
Section: Introductionmentioning
confidence: 99%